2015
DOI: 10.1111/jen.12276
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of efficacy functions for products used to manage corn rootworm larval injury

Abstract: Maize, Zea mays L., is an economically important crop grown throughout the world. Corn rootworm, Diabrotica spp. (Coleoptera: Chrysomelidae), larvae constitute a significant economic threat to maize production in the United States, where yield losses and management costs associated with corn rootworm species exceed $1 billion annually. Furthermore, the introduction of the western corn rootworm, D. virgifera virgifera LeConte, into maize‐producing regions of Europe has made managing corn rootworm larval injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
4
14
0
Order By: Relevance
“…This study confirms that a relatively low level of WCR pyrethroid resistance detected in laboratory bioassays , Souza 2019) is enough to significantly reduce the performance of formulated soil-applied pyrethroid products in the field. A study that analyzed over a decade of research at multiple US maizeproducing sites indicated that nearly 86% less root injury occurred in conventional maize when a soil insecticide was applied in addition to a standard seed treatment (Tinsley et al 2015). Similar results were observed in this study, as treatments tested on the Saunders WCR pyrethroid-susceptible population provided 70-86% less root injury than untreated control plots.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study confirms that a relatively low level of WCR pyrethroid resistance detected in laboratory bioassays , Souza 2019) is enough to significantly reduce the performance of formulated soil-applied pyrethroid products in the field. A study that analyzed over a decade of research at multiple US maizeproducing sites indicated that nearly 86% less root injury occurred in conventional maize when a soil insecticide was applied in addition to a standard seed treatment (Tinsley et al 2015). Similar results were observed in this study, as treatments tested on the Saunders WCR pyrethroid-susceptible population provided 70-86% less root injury than untreated control plots.…”
Section: Discussionsupporting
confidence: 81%
“…Depending on the maize hybrid, pest infestation level, degree of abiotic stresses, and control strategies used, root damage by larval feeding may cause significant yield losses (Metcalf, 1986;Spike and Tollefson 1991;Davis 1994;Urías-López et al 2000;Urías-López and Meinke 2001;Tinsley et al 2013Tinsley et al , 2015. This insect pest also became a major concern for European countries after it was first found in 1992 close to Surcin International Airport in Belgrade (Berger 2001, Miller et al 2005).…”
Section: Chapter 1 Introduction and Literature Review Introductionmentioning
confidence: 99%
“… 45 estimated that under field conditions, one node of root injury was on average associated with a corn yield loss of approximately 15–18%. Further studies are needed to confirm the efficacy 46 of dvssj1 events under field conditions 47 .…”
Section: Discussionmentioning
confidence: 99%
“…After 72 h of feeding, dvssj1 dsRNA treatment (100 ng μ l −1 ) resulted in an overall decrease in neonate length compared to untreated controls ( Supplementary Fig. 4a,b); in some cases, the gut [45][46][47][48] are killed by dsRNA at concentrations of 5 or 50 ng μ l −1 . Fragments of five active targets were selected for LT 50 determination based on dose response assay results (Table 1 and Supplementary Table 2).…”
Section: Identification Of Wcr Gene Targetsmentioning
confidence: 99%
“…Dun et al 44 and Tinsley et al 45 estimated that under field conditions, one node of root injury was on average associated with a corn yield loss of approximately 15-18%. Further studies are needed to confirm the efficacy 46 of dvssj1 events under field conditions 47 .…”
mentioning
confidence: 99%